Tras los pasos de Encino del Val: Anarquismo y Radicalismo en el Sur Andino (1916 – 1930) - Marcelo Ruiz, Johan Francis (2025)
This paper analyzes the militancy of the anarchist Encino del Val during the first decades of the 20th century. In a context of socioeconomic transformation and intellectual renewal in the southern andean region, this character managed to articulate his ideological position with the debates in the región. Therefore, using the transnacional history and intellectual history as theoretical bases, it is possible to trace one of the ways in which anarchism was inserted in the rural areas of the country.